(untitled) (West African Journal on Sustainable Development, 2024)
Technology has over the years, become the driver of businesses and business practices around the globe. There are however corporate organizations that are yet to embrace various technological innovations. As such, this study investigated technological innovation and job satisfaction of Managers and Accountants in Owerri. The study concentrated on registered entrepreneurial entities in the Owerri Senatorial Zone, Imo State. The objectives of the study were to examine the relationship between cloud computing and job satisfaction in entrepreneurial entities; and to assess the level of correlation between mobile applications and job satisfaction in the entrepreneurial entities. The researchers developed a problem statement that captured the research gaps which called for the study. The study was guided by two research objectives, two research questions and two hypotheses. The Davis’ Technology Acceptance Model(TAM) was used to handle the theoretical framework. Empirical reviews were used to beef up the study. The researchers employed the survey research design in the research. A five-point Likert Scale structured questionnaire was the major instrument for data collection. The validity of the instrument was done by showing the questionnaire to research experts for their corrections and inputs. Cronbach Alpha statistic was used for obtaining 0.87as the reliability ratio of the survey instrument. Data analysis was committed to descriptive statistics of mean and standard deviation. Correlation analysis was used to test hypotheses. It was found that each of cloud computing and mobile applications positively and significantly improved job satisfaction of Managers and Accountants in entrepreneurial entities in Owerri. It was concluded that technological innovation was a determinant of job satisfaction of Managers and Accountants in Owerri. The study recommended that entrepreneurial entities should always embrace cloud computing and mobile applications so as to always gain job satisfaction and all round corporate viability.